Profile of the Implementation of the Meaning Model in Science Learning 2013-2022 - Fauziyah Nisyah; Muslimin Ibrahim; Rudiana Agustini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
The meaning model is one of the models needed in the era of rapid globalization in building the character of students. This research was conducted to describe and analyze the implementation of the meaning learning model in Indonesia. The method applied in this research is a library study sourced from previous research that has been published in international and national journals. Based on an analysis of 20 learning articles using the meaning learning model in Indonesia, it can be seen that the meaning learning model has a positive impact on student responses, which can improve student learning outcomes, increase students' understanding of concepts and foster virtuous attitudes towards the surrounding environment. The application of the meaning learning model is able to transmit positive behavior and contains wisdom, this model requires structured planning to support the implementation of the meaning learning model.